Glucose homeostasis during the perinatal period in normal rats and rats with a glycogen storage disorder. - Gain, K R (1981)
The fetal rat mobilizes liver glycogen during parturition for use as a glucose source until the onset of gluconeogenesis at 2 h after birth. A rat strain (NZR/Mh) unable to mobilize liver glycogen because of a phosphorylase b kinase deficiency has been used to assess the importance of liver glycogen in glucose homeostasis of the newborn. In normal rats the mean blood glucose concentration of the fetus measured at various times up to 24 h after natural birth ranged between 3.7 and 5.4 mM. In contrast, fetuses of the affected rats were hypoglycemic before birth (2.02 +/- 0.15 mM), and by 1 h after birth the blood glucose had decreased to 0.74 +/- 0.14 mM. Concentrations increased by 4 h to 1.48 +/- 0.17 mM and by 24 h reached values not significantly different from the normal newborn rats. Changes in plasma insulin over the perinatal period were similar in both groups although concentrations were always significantly lower in the affected rts. The findings demonstrate the crucial role of the fetal liver glycogen store in the maintenance of normoglycemia in the newborn. The normal rat does not develop hypoglycemia when born naturally and left with the mother after birth (in contrast to other studies in which the newborn were taken by cesarian delivery 1 d prematurely and kept in an artificial environment without food). The rats with the glycogen storage disorder experienced severe hypoglycemia without any apparent effects, which raises questions concerning alternative fuels available to and utilized by the newborn.